Reexamining the Validity and Reliability of the Clinical Version of the Iowa Gambling Task: Evidence from a Normal Subject Group - Lin, Ching-Hung; Song, Tzu-Jiun; Chen, Ying-Ying; Lee, We-Kang; Chiu, Yaochu (Frontiers in Psychology, 2013)
Over past decade, the Iowa gambling task (IGT) has been utilized to test various decision deficits induced by neurological damage or psychiatric disorders. The IGT has recently been standardized for identifying 13 different neuropsychological disorders. Neuropsychological patients choose bad decks frequently, and normal subjects prefer good EV decks. However, the IGT has several validity and reliability problems. Some research groups have pointed out that the validity of IGT is influenced by the personality and emotional state of subjects. Additionally, several other studies have proposed that the “prominent deck B phenomenon” (PDB phenomenon) – that is, normal subjects preferring bad deck B – may be the most serious problem confronting IGT validity. Specifically, deck B offers a high frequency of gains but negative EV. In the standard IGT administration, choice behavior can be understood with reference to gain-loss frequency (GLF) rather than inferred future consequences (EV, the basic assumption of IGT). Furthermore, using two different criteria (basic assumption vs. professional norm) results in significantly different classification results. Therefore, we recruited 72 normal subjects to test the validity and reliability of IGT. Each subject performed three runs of the computer-based clinical IGT version. The PDB phenomenon has been observed to a significant degree in the first and second stages of the clinical IGT version. Obviously, validity, reliability and the practice effect were unstable between two given stages. The present form of the clinical IGT version has only one stage, so its use should be reconsidered for examining normal decision makers; results from patient groups must also be interpreted with great care. GLF could be the main factor to be considered in establishing the constructional validity and reliability of the clinical IGT version.